Fabrikasi Engsel Pintu Pagar Baja Panjang 250mm, Lebar 80mm, Tinggi 100mm, Kapasitas 0,7 Set/Jam - Muhammad Afin Khairullah; Syamsul Hadi; Laldy Agum Sartyo; Dafa Ahmad Amrizal; Rizky Khairi Sakha (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Broken or deformed hinges due to the inability to withstand the load of the folding gate door are the problems faced. The purpose of fabrication is to obtain folding gate door hinges from AISI 1020 steel with dimensions of 250x80x3 mm, and a height of 100 mm. The fabrication method includes: design of folding gate door hinges with dimensions of 250x80x3 mm, and a height of 100 mm; cutting 2 sheets of AISI 1020 steel measuring 250x80x3 mm; forging to form a circle with a diameter of 11 mm on the 80 mm wide side; drilling 4 holes with a diameter of 9 mm at the position according to the design; making a hinge shaft from an M10 bolt whose head and thread are connected with a connecting rod to a length of 175 mm; assembling 2 pieces of hinges with a hinge shaft; and quality-dimension-packaging inspection. The fabrication results are a pair of folding gate door hinges made of AISI 1020 steel with dimensions of 250x80x3 mm, and a height of 100 mm with an M10 bolt shaft of 175 mm in length with a production cost of IDR 48,000/unit, and a process duration of 88 minutes/unit which implies that the hinges are ready to be welded to the gate with a maximum load of 50 kg and painted before use.